Legal analysis of labor inequality in Colombia - Gómez Lozano, María Margarita (DIXI, 2021)
Subject and scope: The principle of equality is a pillar of democratic States, as is Colombia. The Political Constitution issued in 1991 gives a new connotation to this principle, which is why it was chosen to demonstrate that it is not complied with in Colombia. The Colombian Constitutional Court has dealt with the subject on multiple occasions, which give the guideline to analyze the scope and repercussion that this fundamental principle has in labor matters, on which the stability of the individual depends in part. Characteristics: The document will allow to study the constitutional and legal provisions on the subject, as well as the position of the jurisprudence and doctrine on the applicability of the principle of equality in labor relations in the country. It is vital to bear in mind that the fundamental principles, and among them the principle of equality, are a guarantee for the citizen participant of the Social State of Law, where the primordial thing is the respect for the dignity and the human person; therefore, something vital for him/her as work is protected. Findings: Equality is a fundamental right in almost all jurisdictions of the world; therefore, reviewing its legal roots and its implementation since the 1991 Charter is preponderant in this study. It is transcendental that equality exists in labor relations, because if it does not exist, inequitable relations will result.